Analysis Of The Effect Of Work Motivation And Compensation On Employee Performance Of Pt. A B C D In South Tangerang - Herudini Subariyanti; Andri Rizko Yulianto (Jurnal Ilmiah Manajemen dan Bisnis, 2021)
This study aims to analyze the effect of work motivation and compensation on employee performance. This research is a type of quantitative descriptive study using primary data sources taken directly from company employees who are actively working in the operational section of PT. ABCD South Tangerang, as a source of research data. The independent variables consist of work motivation and compensation, while the dependent variable is employee performance. The research design was a random sample study which was conducted on 184 samples of employees at PT. ABCD South Tangerang, data collection techniques through questionnaires. Furthermore, the data were analyzed quantitatively by using statistical methods with the help of the SPSS 12.00 computer program, with descriptive analysis techniques, simple correlation, multiple correlation, and basic assumption tests, partial correlation, multiple correlation, F test, t test, determination test. From the research results, it can be concluded that there is a positive and significant relationship between work motivation and compensation on employee performance at PT. ABCD South Tangerang.